MITIGATION VOLTAGE SAG USING DVR WITH HYSTERESIS-ANN CONTROL ON DISTRIBUTION SYSTEM PUJON FEEDER LINE - Arief Trisno Eko Suryo (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2023)
This paper discusses the mitigation of voltage sag in distribution systems. Voltage sag often occurs due to a single line-to-ground short circuit fault. The fault has a major impact on load damage in the Pujon feeder line. Voltage sag can be mitigated by using Dynamic Voltage Restorer (DVR). DVR is one type of custom device that is effective in overcoming voltage sag. DVR requires control in regulating voltage recovery on the Pujon line. This research proposes DVR control using Hysteresis combined with ANN to mitigate voltage sag on Pujon line. Simulation results show that the Hysteresis-ANN control is able to recover the load voltage in phase R on average by 97% due to voltage sag that occurs on the Pujon feeder line.